Influence of sapropel on the activity of intestinal peptidases of broiler chickens - Kuz'mina, V. V.; Skvortsova, E. G.; Pivovarova, E. A.; Bushkareva, A. S.; Vostrova, U. A.; Poltoratskaya, A.V. (Diponegoro University, 2021)
At the beginning of the experiment, the weight of weekly cockerels of the Hisex White egg cross (n = 90) was 64.6 ± 0.47 g. At the age of one week old, 3 groups (30 birds in each group) were formed. They received complete feed. The first group served as a control. The chickens of the second and third groups received combined fodder, in which 3% and 5% of the feed weight was replaced with dry sapropel. The dry sapropel (3% of the daily feed weight) increased the activity of casein-lytic and hemoglobin-lytic peptidases in the chyme by 1.5 (Р<0.05), in large intestine mucosa by 1.3 (Р<0.05) and in small intestine mucosa by 1.7 times (Р<0.01) compared with the control. The increase of sapropel concentration in feed up to 5% did not lead to a further increase in the activity of peptidases. The activity of peptidases were minimal at pH 5 and pH 12 and reached maximal at pH 7–8. The optimal dose of dry sapropel introduced into the diet of chickens to that stimulated the digestive processes is 3% of the mass of feed.